Experimental investigation of usage of POE lubricants with Al2O3, graphene or CNT nanoparticles in a refrigeration compressor - Dağıdır, Kayhan; Bilen, Kemal (Beilstein Journal of Nanotechnology, 2023)
In this study, the use of nanolubricants containing Al2O3, graphene, and carbon nanotubes (CNTs) at different mass fractions in a refrigeration compressor was experimentally investigated. The required electrical power of the compressor was measured to determine the effect of the use of nanolubricants. Nanoparticles used in the preparation of nanolubricants were gradually added to the lubricant to determine the optimum nanoparticle mass fraction for each nanoparticle type. Thus, it was found that the compressor operated safely and efficiently with nanolubricants. Furthermore, the optimum mass fractions were determined to be 0.750% for Al2O3, 0.250% for graphene, and 0.250% for CNTs for operating conditions of this study. As a result, the required electrical power of the compressor decreased by 6.26, 6.82, and 5.55% with the addition of Al2O3, graphene, and CNT nanoparticles at optimum mass fractions of 0.750, 0.250, and 0.250% to the lubricant, respectively, compared to the compressor using pure oil. Moreover, density and dynamic viscosity of the nanolubricant samples used in the experiments were also measured, and their kinematic viscosity, which is an important parameter for lubricants, was calculated. It was determined that the kinematic viscosity continuously increased with increasing nanoparticle fraction. In conclusion, nanolubricants containing nanoparticles above the optimum mass fraction increase the required electrical power of the compressor. It is concluded that nanoparticle fractions should not be used above the optimum value in nanolubricant applications.
Keywords: Al2O3; carbon nanotubes; graphene; nanolubricant; polyolester oil; refrigeration compressor